Hubungan Pernikahan Usia Dini dengan Risiko Tindak Kekerasan oleh Ibu pada Anak Usia Prasekolah di Kelurahan Sumbersari Kecamatan Sumbersari Kabupaten Jember (The Relation between Early Marriage and the Risk of Abusing by Mothers Towards her Preschoolers - Putri Mareta Hertika; Lantin Sulistyorini; Emi Wuri Wuryaningsih (Pustaka Kesehatan, 2017)
Child abuse is arbitrarily action which can hurt children physically and psychologically. One of manycauses of domestic violence towards children is early marriage. This research aimed to analysis thethe relation between early marriage and the risk of abusing by mothers towards her preschoolers inSumbersari, Jember. The research design was analytic survey using cross sectional approach. Thenumber of sample was 77 people and taken by using purposive sample technique. The instrumentsto collect the data were validated and its reliability has been tested. The result of the researchshowed that the respondents who did early marriage had a risk of committing domestic violence upto 29.9% and only 20.8% did not have the risk. The result of chi square test showed that there wasa relation between early marriage and the risk of abusing by mothers towards her preschoolers inSumbersari, jember (p value = 0,015; CI= 95%) with OR = 3,528. There were numerous causes ofchild abuse the pressure from within the family and early marriage. The psychology of women whodid an early marriage was not ready yet for it so that they tended to do child abuse. The solution forthis problem was nurses could cooperate with related institution in the field to hold health trainingfor teenagers related to the impact of early marriage and health training for parents related to howto raise their children.Keywords: Child abuse, early marriage, preschoolers